Design and Kinematic Analysis of a New End-Effector for a Robotic Needle Insertion-Type Intervention System. (4th December 2014) - Moon, Youngjin; Jae Choi, Hyuk; Beom Seo, Joon; Choi, Jaesoon
This paper presents a new end-effector as a key component for a robotic needle insertion-type intervention system and its kinematic analysis. The mechanism is designed as a spherical mechanism with a revolute joint and a curved sliding joint, and its links always move on the surface of a sphere. The remote centre of motion (RCM) of the designed mechanism is placed below the base of the mechanism to avoid contact with the patient's body, unlike the conventional end-effectors developed for needle insertion. For the proposed mechanism, the forward kinematics are solved in terms of input joint parameters and then the reverse kinematics are solved by using the cross-product relationship between each joint vector and a vector mutually perpendicular to the vectors. The kinematic solutions are confirmed by numerical examples.